Frequency-domain iterative learning control of a marine vibrator. (February 2016) - Sörnmo, Olof; Bernhardsson, Bo; Kröling, Olle; Gunnarsson, Per; Tenghamn, Rune
Abstract: To the purpose of marine seismic acquisition, new acoustic sources have been developed to reduce the environmental impact. The use of marine vibrators makes it possible to define emission frequency ranges, consequently allowing limitation of the frequencies that disturb marine animal life. Constructing marine vibrators with high efficiency and linear dynamics is however difficult, and the vibrators suffer from both friction, backlash and high-order harmonics. These nonlinear effects, in combination with drifting dynamics, make the required control a crucial and challenging problem. This paper presents a model-based iterative learning control solution, performed in the frequency-domain. Additionally, an adaptive reidentification algorithm is developed to cope with drifting dynamics. The proposed solutions are successfully evaluated in experiments with a marine vibrator.